2011
DOI: 10.1007/s11434-011-4666-x
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variations in mid-upper tropospheric methane over China from satellite observations

Abstract: Spaceborne measurements by the Atmospheric Infrared Sounder (AIRS) on the EOS/Aqua satellite provide a global view of methane (CH 4 ) distribution in the mid-upper troposphere (MUT-CH 4 ). The focus of this study is to analyze the spatiotemporal variations in MUT-CH 4 over China from 2003 to 2008. Validation of AIRS CH 4 products versus Fourier transform infrared profiles demonstrates that its RMS error is mostly less than 1.5%. A typical atmospheric methane profile is found that shows how concentrations decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The potential change in sources of CH 4 emissions will greatly influence the CH 4 concentration in the atmosphere. However, few studies have been conducted to evaluate the long-term spatiotemporal variations of atmospheric CH 4 concentrations across China [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The potential change in sources of CH 4 emissions will greatly influence the CH 4 concentration in the atmosphere. However, few studies have been conducted to evaluate the long-term spatiotemporal variations of atmospheric CH 4 concentrations across China [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The lowest value of CH 4 (1.759 ppmv) during the spring season (March-May) was appeared at the pristine desert environment at the west and the south-west region While the highest value (1.880 ppmv) appeared on May at the north and north east regions of Iraq. The mean and standard deviation of CH 4 for spring season was (1.834±0.0028 ppmv) which is the lowest during the entire period for the study area and the mean CH 4 Space-borne observation of methane from atmospheric infrared sounder from these sources [8], while the lowest values of CH 4 appeared at the pristine desert environment due to the winds which plays an important role in mixing gases and result into mitigate the concentration of CH 4 on height 800 meters at the rest parts of Iraq. In Iraq "Shamal winds" is the most predominant prevailing strong northwesterly wind; it is steady and blows from the north and northwest.…”
Section: Study Areamentioning
confidence: 82%
“…The remote sensing techniques (satellite measurements) were employed to study the spatiotemporal distributions and variations of CH 4 in various researches for different regions in the world, which provide some information and evidence of CH 4 sources and traces in the atmosphere [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al . [] used CH 4 data from the Atmospheric Infrared Sounder (AIRS) to study middle‐upper tropospheric methane and found that AIRS CH 4 agrees well with the Fourier transform infrared profiles in China [ Zhang et al ., ]. Xiong et al .…”
Section: Introductionmentioning
confidence: 99%
“…CH 4 measurements are available from many different satellites, including ADEOS, GOSAT, SCIAMACHY (Scanning Imaging Absorption Spectrometer for Atmospheric Chartography), AIRS (Atmospheric Infrared Sounder), and IASI [Clerbaux et al, 2003;Frankenberg et al, 2005;Frankenberg et al, 2006;Xiong et al, 2008;Razavi et al, 2009;Saitoh et al, 2012;Crevoisier et al, 2013;Xiong et al, 2013]. Zhang et al [2011] used CH 4 data from the Atmospheric Infrared Sounder (AIRS) to study middle-upper tropospheric methane and found that AIRS CH 4 agrees well with the Fourier transform infrared profiles in China [Zhang et al, 2011]. Xiong et al [2009] found a strong CH 4 plume in the middle troposphere during South Asia monsoon seasons (July-September), providing evidence of strong upward transport moving CH 4 from the surface to middle troposphere [Xiong et al, 2009].…”
Section: Introductionmentioning
confidence: 99%